Variation in GABRA2 Predicts Drinking Behavior in Project MATCH Subjects - Bauer, Lance O.; Covault, Jonathan; Harel, Ofer; Das, Sourish; Gelernter, Joel; Anton, Raymond; Kranzler, Henry R. (Alcoholism, clinical and experimental research, 2007)
Background:  Previous studies demonstrated, and replicated, an association between single nucleotide polymorphisms (SNPs) within the GABRA2 gene and risk for alcohol dependence. The present study examines the association of a GABRA2 SNP with another definition of alcohol involvement and with the effects of psychosocial treatment. Methods:  European‐American subjects (n = 812, 73.4% male) provided DNA samples for the analysis. All were participants in Project Matching Alcoholism Treatment to Client Heterogeneity (MATCH), a multi‐center randomized clinical trial evaluating the efficacy of 3 types of psychosocial treatment for alcoholism: Cognitive Behavioral Therapy (CBT), Motivational Enhancement Therapy (MET), or twelve‐step facilitation (TSF). The daily probabilities of drinking and heavy drinking were estimated during the 12‐week treatment and 12‐month post‐treatment periods. Results:  Subjects homozygous for the allele associated with low risk for alcohol dependence in previous studies had lower daily probabilities of drinking and heavy drinking in the present study. This low‐risk allele was also associated with a greater difference in drinking outcomes between the treatments. In addition, it enhanced the relative superiority of TSF over CBT and MET. Population stratification was excluded as a confound using ancestry informative marker analysis. Conclusions:  The assessment of genetic vulnerability may be relevant to studies of the efficacy of psychosocial treatment: GABRA2 genotype modifies the variance in drinking and can therefore moderate power for resolving differences between treatments.